2019
DOI: 10.1001/jamanetworkopen.2019.4765
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety of Direct-Acting Antiviral Agents for Hepatitis C

Abstract: Key Points Question Are patients with hepatitis C who receive direct-acting antivirals at increased risk for adverse events compared with those who do not receive these agents? Findings In this cohort study of 33 808 patients in 3 health systems, direct-acting antiviral exposure was associated with lower odds of experiencing the following adverse events: death, multiple organ failure, hepatic decompensation, acute-on-chronic liver event, and arrhythmia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 34 publications
5
39
0
5
Order By: Relevance
“…Several well-designed, robust clinical trials have demonstrated the safety (147) and high curative efficacy of glecaprevir/pibrentasvir (148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) and sofosbuvir/ velpatasvir (159)(160)(161)(162)(163)(164) among treatment-naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real-world cohort studies for both glecaprevir/pibrentasvir (165)(166)(167) and sofosbuvir/velpatasvir.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultmentioning
confidence: 99%
“…Several well-designed, robust clinical trials have demonstrated the safety (147) and high curative efficacy of glecaprevir/pibrentasvir (148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) and sofosbuvir/ velpatasvir (159)(160)(161)(162)(163)(164) among treatment-naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real-world cohort studies for both glecaprevir/pibrentasvir (165)(166)(167) and sofosbuvir/velpatasvir.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultmentioning
confidence: 99%
“…Despite the rising prevalence of SO among LT patients, especially in the subgroup of NASH ( 11 ), the optimal management of obese and overweight LT candidates remained undetermined. Increased body mass index is commonly observed after LT ( 30 ), and it appears that much of this weight gain is an increase in fat mass ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 32% of the US population is considered to be obese, based on the body mass index (BMI) cut-off of 30 kg/m 2 ( 9 , 10 ). It is common knowledge that obesity increases the risk of perioperative complications ( 11 ) but how it affects the outcomes of LT in the long-term remains unclear. Studies have demonstrated that sarcopenia is an independent predictor of mortality, sepsis, and a more extended hospital stay after living donor LT ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Несколько хорошо спланированных и надежных клинических испытаний продемонстрировали безопасность [16] и высокую лечебную эффективность схемы глекапревир/пибрентасвир и комбинации софосбувир/велпатасвир среди наивных лиц без цирроза, независимо от генотипа ВГС [17][18][19][20][21]. Эти данные были подтверждены в реальных когортных исследованиях как для схемы глекапревир/пибрентасвир, так и для комбинации софосбувир/велпатасвир [22][23][24].…”
Section: упрощенный алгоритм лечения гепатита с для лечения наивных вunclassified